98.9k views
1 vote
5. Solve by Substitution:
4x + y = 11
y = 3x - 3

User Queeg
by
5.9k points

2 Answers

4 votes

Answer:

y=-x-3

Explanation:

User Alrick
by
6.2k points
5 votes

Answer:

(2, 3 )

Explanation:

Given the 2 equations

4x + y = 11 → (1)

y = 3x - 3 → (2)

Substitute y = 3x - 3 into (1)

4x + 3x - 3 = 11, that is

7x - 3 = 11 ( add 3 to both sides )

7x = 14 ( divide both sides by 7 )

x = 2

Substitute x = 2 into (2) for corresponding value of y

y = (3 × 2) - 3 = 6 - 3 = 3

Solution is (2, 3 )

User Kenny Horna
by
5.2k points